STUDI ESTETIKA TARI PIRIANG MALUNYAH DI DESA SIGINTIR KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Ayulia Marentika; Darmawati Darmawati; Desfiarni Desfiarni (SENDRATASIK UNP, 2013)
Absract This research is aimet to descripbe the estetical study of piriang malunyah dance in sigintir,sungai pagu regency, solok selatan.the research are primary and secondary data. The technigue of data collections are references from the library, observation, interview, and documentation. From the result, it is found thet the shaperg of piriang malunyah dance are in the from, and the arrangenent of its movement it is also found that there is an idea of farmers activity in the society in piriang malunyah dance.   Kata kunci : Estetika, Tari Piriang Malunyah